Characterization of dissimilar friction stir welded joints of aluminium alloys by simulation and experimentation. Issue 1 (March 2021) - Kumar, R; Kumar, A; Chattopadhyaya, S; Kumar, U; Gope, D
Abstract: The present work "Characterization of dissimilar friction stir welded joints of aluminium alloys by simulation and experimentation" is a combination of simulation and experimental work. In first part of the work friction stir welding (FSW) process is simulated in abacus software and then second part is based on the experimental work of friction stir welded joints of dissimilar aluminium alloys. In abacus, FSW process is well simulated. In this part heat generation profile during FSW is obtained in work-piece as well as in tool. In second part two alloys i.e. AA 5083 and AA 6061 is welded with friction stir welding process. Three process parameters were selected for welding. Three tool rotational speed is selected i.e. 500 rpm, 710 rpm and 900 rpm and one welding speed i.e. 25 mm/min. All the three welded samples were properly machined and different testing samples were prepared. Mechanical and micro-structural properties were studied on the variation of process parameters. From tensile test it can be concluded that with increase in tool rotational speed tensile strength increases. In all cases brittle fracture was observed. From microstructure study fine grains are observed in weld nugget zone.